Crystal habit-directed gold deposition on pyrite: Surface chemical interpretation of the pyrite morphology indicative of gold enrichment. (1st November 2019) - Xian, Haiyang; He, Hongping; Zhu, Jianxi; Du, Runxiang; Wu, Xiao; Tang, Hongmei; Tan, Wei; Liang, Xiaoliang; Zhu, Runliang; Teng, H. Henry
Abstract: The occurrence of the 2 1 0 shape of pyrite crystals has been used as an empirical indicator for gold enrichment in ore deposits. Such indicating, also called 'typomorphism' in ore mineralogy, was conventionally attributed to environmental factors such as sulfur fugacity and temperature and pressure conditions in the ore-forming hydrothermal fluid. Here we show that the crystal-face specific redox reactivity of pyrite is also an important governing potency that drives gold enrichment in the pyrite crystals with particular shapes. This conclusion was drawn from data compiled from chemical analysis of field samples, laboratory testing of gold deposition on natural pyrite crystals, as well as theoretical calculations. Kinetic measurements of gold reductive deposition first revealed the highest precipitation rate on the 2 1 0 faces, particularly when pyrite crystals are enclosed by complex forms containing 2 1 0. Corroborating with the experimental observations, density functional theory (DFT) calculations further indicated that the 2 1 0 possesses a high adsorption energy for gold, a high energy state of the highest occupied molecular orbital and consequently a low Eh. These results afford evidence supporting the view that the face specific reactivity, an intrinsic property of crystal, plays an important role in the gold concentration in pyrite and the occurrence of specific pyrite shapes. Our findings not only provide a surface chemical view for understanding the empirical prospecting method but also exemplified the significance of crystal face specific-reactivity in understanding crystallographic orientation related geochemical processes. The crystal face specific reactivity may be a critical factor controlling geochemical reactions at mineral-water interface, such as prebiotic synthesis on pyrite surfaces and mineral-water interface controlled kinetic isotope fractionation.